Fatal Multisystem Toxicity and Vesiculobullous Eruptions Following Brake Fluid Poisoning: A Case Report - AziziKia, Hani; Amarian, Monireh; Chitzan-Zadeh, Kosar; sahranavard, Mohammad; Sarvestani, Zahra; Yekesadat, Seyed Meysam (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Ethylene glycol and diethylene glycol, commonly found in automotive brake fluids, are highly toxic agents. While their nephrotoxic and neurotoxic effects are well documented, delayed and atypical systemic manifestations are less frequently reported. Case Presentation: We describe a 53-year-old male who presented with acute epigastric pain after ingesting 50 mL of brake fluid. Initial assessment and laboratory findings were unremarkable. However, he returned 36 hours later with acute kidney injury, high-anion-gap metabolic acidosis, and worsening clinical status. Over the subsequent days, he developed progressive multi-organ failure, including hypoxemia, altered consciousness, optic disc edema, intraretinal hemorrhages, and visual impairment. By day seven, he demonstrated brainstem areflexia and diffuse cerebral edema, requiring intubation. Dermatomal vesiculobullous eruptions suggestive of viral reactivation and superinfected pressure ulcers. Despite hemodialysis and supportive treatment, he died on day 43 following cardiorespiratory arrest. Conclusion: This case highlights rare, delayed manifestations of brake fluid poisoning, including optic neuropathy, dermatomal vesiculobullous eruptions, and progressive brainstem dysfunction. Such atypical features may delay diagnosis and complicate management. Brake fluid poisoning can present with evolving multisystem complications beyond the acute phase. Extended observation and a multidisciplinary approach are crucial, even in patients initially presenting with stable vital signs